Rational filters - Hassan Nosratabadi (Rutgers University, Department of Economics, 2017)
It has been widely documented that reference points influence the choice. If references affect choice by attracting attention towards an alternative, what can be said about the joint effect of the references? Assuming that references form preferences, or are rational filters, this paper extracts a reference-dependent choice model with joint referential effects from WARP. Assume that a DM has an ''unfiltered'' pairwise preference which is inferred from her choice over doubletons. The DM's uses her rational filters consecutively on the pairwise preference in order to finalize her choice.
Keywords: D11; D81; 330; Rational Preferences; Rational Filters; Revealed Preference; Referential Decision Maker; WARP Decompositions